“The main aspects of creating an urban landscape in oil” - Luiza Albastova (Periodica Journal, 2022)
The cityscape is always an atmospheric picture that conveys the spirit of time. This is a reflection of the moment of time in the eyes of the artist or a reflection of the artist's inner world in everything that the artist sees around. The cityscape is not quite an ordinary genre. We think that the landscape is bushes, trees, a field, a river or a hut. In the urban landscape the city is equated with the surrounding nature. Somewhere it is inscribed in nature, somewhere it displaces it, fights with it and even wins. If man is part of nature then everything that man does is also part of nature.
Keywords: everything; nature; landscape; displaces